KEPEMIMPINAN PENDIDIKAN MUTU - Amiruddin, Amiruddin; Annisa, Annisa; Arianto, Arianto (Universitas Dharmawangsa, 2019)
Leadership is a central point and determinant of policy activities that will be implemented in the organization and is a very important factor in determining the achievement of organizational goals that have been set. It is the essence of organizational management, basic resources and the central point of every activity that occurs in an organization. Educational leadership is the process of influencing and guiding a leader to educators and education personnel to carry out educational and research tasks using existing educational facilities, both individually and in groups so that educational goals are achieved effectively and efficiently. The quality of education is an evaluation of education that involves all aspects of education starting from the input, process and output of education that illustrates the quality of school performance regarding the achievement of educational goals that are in accordance with the standards and satisfaction of education stakeholders. The values needed by educational leadership to produce high quality educational institutions, namely: 1) Vision and symbols, 2) MBWA (Management by Walking About), 3) Focus on students 4) Autonomy, experimentation and anticipation of failure, 5) Creating sense of kinship, 6) Sincerity, patience, enthusiasm, intensity, and enthusiasm.